Deep acting and bad faith: a Sartrean treatment of emotion work. (14th July 2008) - Ashman, Ian
This paper explores emotion work from a Sartrean perspective. It argues that a Sartrean explanation of emotions may offer a novel approach to analysing emotions at work by countering the deterministic and somewhat negative emphasis that pervades the mainstream. The efficacy of Hochschild's distinction between deep and surface acting is questioned with particular attention being paid to its links with authenticity. Sartre's concept of bad faith is introduced as a means of highlighting the limitations of the distinction and a way of influencing future research. Conclusions are drawn as to how a Sartrean perspective may influence important emotion work themes.